Prevention of dystrophic pathology in severely affected dystrophin/utrophin-deficient mice by morpholino-oligomer-mediated exon-skipping. - Goyenvalle, A; Babbs, A; Powell, D; Kole, R; Fletcher, S; Wilton, S; Davies, K (2010)
Duchenne muscular dystrophy (DMD) is a severe neuromuscular disorder caused by mutations in the dystrophin gene that result in the absence of functional protein. Antisense-mediated exon-skipping is one of the most promising approaches for the treatment of DMD because of its capacity to correct the reading frame and restore dystrophin expression, which has been demonstrated in vitro and in vivo. In particular, peptide-conjugated phosphorodiamidate morpholino oligomers (PPMOs) have recently been shown to induce widespread high levels of dystrophin expression in the mdx mouse model. Here, we report the efficiency of the PPMO-mediated exon-skipping approach in the utrophin/dystrophin double-knockout mouse (dKO) mouse, which is a much more severe and progressive mouse model of DMD. Repeated intraperitoneal (i.p.) injections of a PPMO targeted to exon 23 of dystrophin pre-mRNA in dKO mice induce a near-normal level of dystrophin expression in all muscles examined, except for the cardiac muscle, resulting in a considerable improvement of their muscle function and dystrophic pathology. These findings suggest great potential for PPMOs in systemic treatment of the DMD phenotype.